Decolonising the Viking Story in the North Atlantic - Griffiths, DW (Norwegian Archaeological Society, 2025)
This paper juxtaposes the ways in which literary, historical, and archaeological narratives of the Viking Age have been instrumentalised for political purposes in the high medieval and modern periods. Written at a time of increased political tension in Iceland, Orkney inga saga arguably sought to legitimise Norwegian territorial claims over parts of the North Atlantic with its narrative of the earlier settlement era. This claim is traced forward from the 13th century to the nationalist and later neo-imperialist stance of 19th and early 20th century Norwegian attitudes to the Viking Age. Scandinavian and British scholarship of the culture historical era produced a colonial and racial paradigm for the Viking expansion which was dominant for most of the 20th century, but now requires deconstruction and revision. New insights from recent scientific and humanistic research have helped to break down the dominance of culture-history and a reinvigorated subject has emerged.